The legal implications of International Environmental Law Principles on Marine Pollution in the Gulf of Guinea (African Journal of Law and Politics, 2025)
International environmental law principles remain central in the enforcement of environmental engagements on marine pollution, whether locally or internationally. From qualitative and desk literature gathered, there is an indication that most of these principles are used by the west to control the less or developing nations economic growth. Objectively, there is a tussle between the wealthy nations considered as strong against developing nations, regarded as weak in the management of environmental options. It was realized that the incentive-based approach has not been very efficient in respecting the principle of reciprocity by western nations vis-à-vis developing countries or emerging nations. In the just ended COP21 conference in Paris, African countries continue to demand a just and sincere compensation from the wealthy nations for reserving their environment, either within polluter pay or precautionary principles. It’s now generally accepted that, in addition to Incentive-Base Approach, there is a need to reformulate international environmental principles to give equal obligations to all nations in the domain of environment.